(untitled) - Andrieux, Maurice (New York, 1968)
Contents: Ancient Rome; medieval Rome; the renaissance; the counter-reformation; Baroque Rome; the final century of papal Rome
Keywords: Ý,Rome (Italy); History; Lịch sử